Marketing Language in Tourism Discourse: Corpus Based Study on Personal Pronoun â€œYouâ€ - Zein, T. Thyrhaya; Afdal, Taufik (Linguistik, Terjemahan, Sastra (LINGTERSA), 2024)
This paper investigates the use of the personal pronoun "you" in tourism discourse through a corpus-based study of the Lonely Planet website. As a central element in engaging readers, the pronoun "you" serves to directly address and involve the audience, making the discourse more interactive and persuasive. By analyzing a comprehensive corpus of travel-related texts, this study examines how "you" is strategically utilized to create a personalized experience, guide the reader's journey, and establish a conversational tone in tourism content. The research uncovers patterns in the usage of "you" across various contexts and topics within the website, providing insights into its role in shaping audience perception and enhancing the effectiveness of tourism marketing. This study contributes to a better understanding of linguistic strategies in digital tourism discourse, offering valuable implications for both researchers and professionals in the tourism industry.